Comparison of numerical and experimental results of water -pipe wall interaction - Heidari, Ali; Ghassemi, Poria (International Journal of Engineering and Technology, 2015)
Tube wall analysis on unsteady network flow of pipe shows that the column is separated when it reached to vapor pressure. In this study, we experiment dynamic behavior of fluid distribution pipe system. The model used in is a straight suspended pipe, which is striked by a solid steel bar. Then the results of pressure change in different parts of pipe has been studied and compared with valid results. Â